The contribution of students' psychological conditions in achieving basketball learning outcomes - Prabowo Yudho, Firdaus Hendry; Aryani, Mela (Jurnal Maenpo : Jurnal Pendidikan Jasmani Kesehatan dan Rekreasi, 2024)
A person's ability to perform motor movement tasks based on his awareness and psychological state is always interesting to discuss. This also applies to basketball sports activities in the school environment both within the scope of physical education and extracurricular activities. This research aims to accurately determine the relationship between cognitive anxiety, somatic anxiety, and self-confidence with the results of the free throw shot in basketball. The population of this study was basketball student-athletes totaling 42 people, 24 men and 20 women (± 17 years old), and this research study was conducted after school time ended. The instrument used in this research was the form of questionnaire to measure the level of anxiety with the Competitive State Anxiety Inventory-2 (CSAI-2) questionnaire created by Martens, Vealey, and Burton (1990) which consists of 27 questions including Cognitive State Anxiety, Somatic State Anxiety, and Self-Confidence. The research data results were then processed using descriptive and inferential correlational statistical techniques. The research results show that the cognitive anxiety and free throw, and the somatic anxiety and free throw both correlation test results have an insignificant value with the correlation data obtained as of p .471 and p .661. The results of the correlation test between self-confidence and free throw have an insignificant value with correlation data results p .642, all the correlation tests are within the significance level of ?.05.This study shows that there is a relationship between cognitive anxiety, somatic anxiety, and self-confidence regarding the results of free throw shooting in basketball, but there is no significant relationship between cognitive anxiety, somatic anxiety, and self-confidence towards the results of free throw shot.